2011
DOI: 10.1001/archsurg.2011.157
|View full text |Cite
|
Sign up to set email alerts
|

Transforming the Culture of Surgical Education

Abstract: Promoting a culture of teaching may encourage students to choose a surgical career. Teaching in a human factors (HF) curriculum, the nontechnical skills of surgery, is associated with surgeons' stronger identity as teachers and with clinical students' improved perception of surgery and satisfaction with the clerkship experience. Objective: To describe the effects of an HF curriculum on teaching culture in surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…Of these studies, 11 showed that clinical exposure improves student knowledge of and interest in surgery. [55][56][57][58][59][60][61][62][63][64][65] Clerkship changed student perception of surgery and the surgical lifestyle in 6 of the studies we identified. [66][67][68][69][70][71] This has a variable impact on student interest in a surgical career.…”
Section: Clinical Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Of these studies, 11 showed that clinical exposure improves student knowledge of and interest in surgery. [55][56][57][58][59][60][61][62][63][64][65] Clerkship changed student perception of surgery and the surgical lifestyle in 6 of the studies we identified. [66][67][68][69][70][71] This has a variable impact on student interest in a surgical career.…”
Section: Clinical Exposurementioning
confidence: 99%
“…[55][56][57][58][59][60][61][62][63][64][65] Specifically, students with early interest in surgery were more likely to seek out surgical experiences and were more inclined to report a positive clerkship experience, thereby artificially strengthening the association be tween exposure and interest.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore there is no agreement on evaluation of medical teacher effectiveness [18,19]. Most of the studies regarding teachers’ perceptions of effective teacher are either focussed on a specific subgroup of the medical profession like clinical skills lab [16] or surgical education [20], or have been done in non-medical or allied medical fields such as language [21], agriculture [22], business [23], nursing [24] and pharmacy [13]. Terese Stenfors-Hayes et al [25] have said, “Most studies so far within this field have focused on teaching per se, whilst few focus on being a teacher”.…”
Section: Introductionmentioning
confidence: 99%
“…Un total de 252 estudiantes (65,87% mujeres), denotando una tasa de respuesta de 50%, fueron incluidos en el análisis. La edad promedio de los participantes fue 22,20 ± 1,92 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) años. El promedio global de la intención de optar por una carrera en cirugía fue 3,15 ± 1,34 (IC 95% 2,99-3,32).…”
Section: Resultsunclassified
“…Nuestros hallazgos tienen varias explicaciones. La intención de "convertirse" en cirujano denota la voluntad individual para desarrollar una identidad profesional en un complejo ambiente de práctica, cultura y normas, que implican un estilo de vida y práctica profesional exigentes [25][26][27] . Creemos que el estilo de vida y la práctica son factores que continúan siendo atractivos para quienes quieren optar por la especialidad, y evocan aspectos emocionales, pasionales y relacionados con los valores de la profesión 28,29 .…”
Section: Tabla 1 Estadísticas Descriptivas Y Correlaciones De Las Vaunclassified